Exploring the effectiveness of technology-based learning on the educational outcomes of undergraduate healthcare students: an overview of systematic reviews protocol - Muhammad Hibatullah Romli; Manraj Singh Cheema; Muhammad Zulfadli Mehat; Nur Fariesha Md Hashim; Hafizah Abdul Hamid (BMJ Open)
Introduction Rapid technology development due to the introduction of Industrial Revolution 4.0 and Internet of Things has created a demand and gradual transition from traditional teaching and learning to technology-based learning in higher education, including healthcare education. The COVID-19 pandemic has accelerated this process, with educators now required to quickly adapt to and adopt such changes. The abundance of available systematic reviews has made the effectiveness of such approaches ambiguous especially in healthcare education. Therefore, a protocol of the overview of systematic reviews (OoSR) is planned to extrapolate the effectiveness of technology-based learning in undergraduate healthcare education.Methods and analysis Scopus, CINAHL, Academic Search Complete, Cochrane Library, MEDLINE and Psychology and Behavioral Sciences Collection databases were selected. Screening was conducted independently by at least two authors and the decision for inclusion was done through discussion or involvement of an arbiter against a predetermined criteria. Included articles will be evaluated for quality using A MeaSurement Tool to Assess systematic Reviews and Risk of Bias in Systematic Review tools, while primary systematic review articles will be cross-checked and reported for any overlapping using the ‘corrected covered area’ method. Only narrative synthesis will be employed according to the predefined themes into two major dimensions—theory and knowledge generation (focusing on cognitive taxonomy due to its ability to be generalised across disciplines), and clinical-based competence (focusing on psychomotor and affective taxonomies due to discipline-specific influence). The type of technology used will be identified and extracted.Ethics and dissemination The OoSR involves analysis of secondary data from published literature, thus ethical approval is not required. The findings will provide a valuable insight for policymakers, stakeholders, and researchers in terms of technology-based learning implementation and gaps identification. The findings will be published in several reports due to the extensiveness of the topic and will be disseminated through peer-reviewed publications and conferences.PROSPERO registration number CRD4202017974.